Monocyte count / HDL cholesterol ratio: A new marker in diabetic retinopathy - Solmaz, Ihsan; Karahan, Mine (Annals of Medical Research, 2021)
Aim: Diabetic retinopathy (DRP) makes up a significant portion of visual impairments. DRP is divided into proliferative and non-proliferative forms. Monocytes contribute to inflammation, whereas HDL reinforces the reversal of inflammation through promoting anti-inflammatory pathways. The monocyte-to-HDL cholesterol ratio (MHR) is one of the indicators that have been included in recent inflammation studies. This study aims to investigate the diagnostic value of MHR and whether it can be utilized as an indicator of diabetic retinopathy.Materials and Methods: This study includes patients diagnosed at least 5 years ago with type II diabetes mellitus (DM) who are ≥ 18 years old and have an HbA1c value > 6.5. The control group is made up of patients aged ≥ 18 years that presented to the outpatient clinic for other ailments of the eye. The data were prospectively recorded through the hospital information system. The subjects were divided into 3 groups: proliferative retinopathy, non-proliferative retinopathy, and control. Results: The study included a total of 200 subjects: 70 patients with diabetic non-proliferative retinopathy, 87 patients with diabetic proliferative retinopathy, and 43 patients without retinopathy. There were 92 male (46%) and 108 female patients (54%). The mean age was 66.35 ± 11.3 years (19-96). In this prospective observational study, we found that the MHR values of experimental and control groups were significantly different (p = 0.046). The post hoc Tukey's honest significant difference (HSD) test revealed a statistically significant difference between the control and proliferative retinopathy groups (p = 0.040), but not the non-proliferative retinopathy group (p = 0.125).Conclusion: MHR has diagnostic potential for diabetic retinopathy, especially for the proliferative form.
Keywords: Monocyte-to-HDL ratio; retinopathy; diabetes